2005
DOI: 10.1128/jb.187.9.3002-3012.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of WaaL, a Ligase Associated with Linking O-Antigen Polysaccharide to the Core of Pseudomonas aeruginosa Lipopolysaccharide

Abstract: The O antigen of Pseudomonas aeruginosa B-band lipopolysaccharide is synthesized by assembling Oantigen-repeat units at the cytoplasmic face of the inner membrane by nonprocessive glycosyltransferases, followed by polymerization on the periplasmic face. The completed chains are covalently attached to lipid A core by the O-antigen ligase, WaaL. In P. aeruginosa the process of ligating these O-antigen molecules to lipid A core is not clearly defined, and an O-antigen ligase has not been identified until this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 64 publications
(61 reference statements)
7
119
1
Order By: Relevance
“…aeruginosa plays a role in flagellar biogenesis in this species (Abeyrathne et al, 2005). However, this is not the case in A. hydrophila galU mutants because the flagellar biogenesis is unaffected.…”
Section: Discussionmentioning
confidence: 73%
“…aeruginosa plays a role in flagellar biogenesis in this species (Abeyrathne et al, 2005). However, this is not the case in A. hydrophila galU mutants because the flagellar biogenesis is unaffected.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, these results are consistent with the normal production of O-antigen precursors that cannot be attached to the core OS because of a wapR knockout. Our group has previously shown that this type of undecaprenol phosphate-linked O-antigens is sensitive to phenol (1,4,20), and when LPS from the wapR mutant was prepared by the hot aqueous phenol method of Westphal and Jann (31) rather than the fast method of Hitchcock and Brown (10), A-band and B-band O antigens were not detected by either SDS-PAGE or Western immunoblotting (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…These repeat units are then sequentially assembled to a growing chain by the polymerase Wzy, and the length of the growing polysaccharide is determined by the polymerase co-polymerase (PCP) Wzz [17]. The complete periplasmic O-antigen chain is attached by the ligase WaaL to the lipid A-core moiety anchored to the outer leaflet of the IM [1], forming smooth-LPS.…”
Section: Introductionmentioning
confidence: 99%